The Moffats - Estes, Eleanor, 1906-1988.; Slobodkin, Louis, 1903-1975 (San Diego : Harcourt, 2001)
Relates the adventures and misadventures of the four Moffat children living with their widowed mother in a yellow house on New Dollar Street in the small town of Cranbury, Connecticut.
"An Odyssey/Harcourt Young Classic"--verso t.p.
Sequel: The middle Moffat.
Keywords: Siblings -- Fiction; Family life -- Connecticut -- Fiction; Connecticut -- Fiction